Conocimientos, actitudes y prácticas en salud oral de padres y/o cuidadores de niños de la primera infancia de la I.E.D Escuela Normal Superior de Junín Cundinamarca en el año 2022 (2022)
Objective: To evaluate the knowledge, attitudes and practices in oral health of parents and/or caregivers of early childhood children of the I.E.D Escuela Normal Superior de Junín Cundinamarca in the year 2022. Material and methods: A cross-sectional descriptive observational study was carried out with a sample of 206 parents and/or caregivers of the Departmental Educational Institution Escuela Normal Superior in the Municipality of Junín Cundinamarca, the data collection instrument validated by Canisales & Malpica (2018) was applied. of the Universidad del Bosque to determine and evaluate the level of knowledge, attitudes and practices in oral health of parents and/or caregivers.